1987
DOI: 10.1161/01.cir.76.4.860
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in endocardial activation of the canine papillary muscle early and late after myocardial infarction.

Abstract: Permanent coronary occlusion produces time-dependent changes in surviving subendocardial cellular properties. We compared the functional alterations in Purkinje (P) and ventricular muscle (VM) activation early (24 hr) and late (4 weeks or greater) after permanent coronary occlusion in an in vitro preparation of canine papillary muscle. High-density extracellular (1 to 2 mm resolution) and selected intracellular recordings were made in five animals early and seven animals late during stimulation of a free-runni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…However, in this as well as another study (13), slow conduction was demonstrated in Purkinje fibers that were present within regions of scar. It is unclear whether the conduction delay was present only in the Purkinje fibers or also at the Purkinje-myocardial tissue interface.…”
Section: Discussionsupporting
confidence: 43%
“…However, in this as well as another study (13), slow conduction was demonstrated in Purkinje fibers that were present within regions of scar. It is unclear whether the conduction delay was present only in the Purkinje fibers or also at the Purkinje-myocardial tissue interface.…”
Section: Discussionsupporting
confidence: 43%
“…The values of coupling conductance we used are at least one order of magnitude smaller than the values of gap junctional conductance required for normal conduction in ventricular tissue [14,31]. Under conditions of myocardial ischemia, discrete groups of surviving cells are separated from other groups of cells by connective tissue [10,18,37]. The slow conduction and fractionated waveforms that are characteristic of conduction in ischemic tissue are indications of the successive activation of groups of cells for which the intergroup conductance is limiting the conduction.…”
Section: Scaling Of the Modelmentioning
confidence: 99%
“…Our use of a model of elements of variable sizes can be scaled to represent the conduction between groups of cells under the conditions that, within each group, the cells of the group are themselves well coupled to each other and essentially isopotential. That this condition is met under certain ischemic conditions is indicated by the brief duration of each compo- nent of the fractionated signals and also from direct microelectrode recordings from cells within the groups [18]. Thus, the conduction between groups of 100 cells ("size 100 elements") connected by a conductance of 5 µS would have the same characteristics of electrical loading and also the success or failure of conduction as one would observe between single cells ("size 1 elements") connected by a conductance of 50 nS.…”
Section: Scaling Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Action potentials in these regions have prepotentials and notches due to electrotonic interactions with nearby cells. 4 During acute ischemia, excessive concentrations of catecholamines are observed within the unperfused myocardium. 5 Depletion of catecholamines or treatment with ␤-blockers decreases the incidence of ischemia-induced arrhythmias.…”
mentioning
confidence: 99%